Skin collagen defects in a patient with juvenile hyaline fibromatosis. Issue 3 (September 1995) - Lubec, B; Steinert, I; Breier, F; Jurecka, W; Pillwein, K; Fang-Kircher, S
Abstract : Juvenile hyaline fibromatosis is a rare disorder characterised by multiple subcutaneous tumours, gum hypertrophy, muscle weakness, and flexion contractures of the large joints. Histology shows an abundance of a homogenous, amorphous, acidophilic extracellular matrix in which spindle shaped cells are embedded forming minute streaks. It has been previously suggested that collagen abnormalities may be involved. A 14 month old girl with this syndrome is described in whom postmortem western blot studies were performed. These studies revealed an absent pro-alpha 2(I) chain and an absent collagen type III chain in skin but not in the other organs examined.